Analysis of the Status and Trends of Chinese Clinical Practice Guideline Development Between 2010 and 2020: A Systematic Review - Zhang, Rong; Yan, Si-yu; Wang, Yun-yun; Huang, Qiao; Ren, Xiang-ying; Tan, Ran; Deng, Yu-qing; Su, Lin-xia; Wang, Yong-bo; Zhao, Zheng-rong; Jin, Ying-hui (Frontiers in Medicine, 2021)
Objective: This study aimed to systematically review the status and trends of Chinese clinical practice guidelines (CPGs) during the time period 2010–2020 and explore their methodological characteristics. Then, based on the strengths and weaknesses in development, offer several recommendations for the quality improvement which will serve as a reference for the users and developers of CPG. Introduction: With the development of evidence-based medicine (EBM), the CPGs play an increasingly important role in healthcare decision-making both in China and worldwide. Inclusion criteria: The CPGs that have been used to help the health professionals in the healthcare decision-making were included. Methodology: The China National Knowledge Infrastructure (CNKI) and WanFang databases were searched from 2010 to 2020 for the studies describing the general and methodological characteristics of Chinese CPGs. Comparisons of the methodological characteristics between the groups were conducted using the chi-square test or Fisher's exact test. The M-K test was adopted to identify the monotonically increasing or decreasing trends of methodological characteristics over the timespan. Results: A total of 2,654 CPGs fulfilled the inclusion criteria. The quantity and quality of the guidelines developed in China have improved over the time span. From 2010 to 2020,the guidelines had differing characteristics and covered a wide range of subjects. In total, 2,318(87.34%) guidelines focused on Western Medicine. Eight (0.30%) had been developed for patient versions of guidelines, 10(0.38%) were tentative guidelines, and 16(0.60%) were rapid advice guidelines. Medical specialty societies (including their branches) (71.1%) were the main guideline makers. The most addressed diseases were neoplasms (14.43%). The target population is mainly adults (84.97%). The methodological quality of consensus-based (CB)-CPGs was obviously lower than evidence-based (EB)-CPGs. Except for the item, “recommendations were based on evidence of systematic reviews,” there were statistical differences in all other methodological items between the EB-CPGS and CB-CPGS (P < 0.01). Higher methodological quality has been observed in EB-CPGs. All the data relating to the methodological characteristics indicated that higher methodological quality was present in the guidelines using GRADE (P < 0.01). Conclusion: The quantity and quality of the guidelines developed in China have improved between 2010 and 2020. CB-CPGs have also paid attention to the methodology quality, but obviously, this is lower than that in the EB-CPGs.